Particle Nucleation Using Different Initiators in the Miniemulsion Polymerization of Styrene - Ronco, Ludmila Irene (2015)
In miniemulsion polymerization, droplets nucleation is the key factor to ensure the production of polymer particles with a desired composition. The influence of the initiation on droplets nucleation is even conflicting and it has not been completely considered. The result of employing different initiators systems on the nucleation mechanism and kinetics in the polymerization of stable styrene/polystyrene miniemulsions with varied droplets size is here discussed. The employed initiation systems provide all combinations between the phase (aqueous or organic) where initiation mainly occurs and the phase affinity of the produced radicals. Latexes with different contribution of the droplets nucleation were synthesized according to the employed initiation system and the droplets size of the miniemulsion. The results here presented could be used as a guide for choosing the initiation system to achieve the required contribution of the droplets nucleation.